Carboxyhemoglobin levels in preterm neonatal late-onset sepsis: To predict or not to predict - ÖZEK, EREN (My University, 2023)
Background: In this study, we aimed to evaluate carboxyhemoglobin (COHb) levels in diagnosing late-onset sepsis (LOS) in preterm neonates. Methods: The records of culture-positive LOS in preterm neonates hospitalized in NICU from January 2017 to July 2022 were reviewed. COHb levels, C-reactive protein, procalcitonin, and neutrophil to lymphocyte ratio of septic preterm infants were compared to controls. In addition, serial COHb levels measured within six hours before or 24h after blood culture sampling, three to seven days prior, and three to five days after starting antimicrobial therapy were retrieved from patient records. Results: The study included 77 blood-culture-positive preterm infants and 77 non-septic controls. During the LOS episode, the COHb values were found to be significantly increased (median: 1.8, IQR: 1.4-2.5) when compared to the control group (median: 1.2, IQR: 0.8-1.6) (p 1.5%, the test\"s sensitivity was 64.94%, the specificity was 72.73%, the positive predictive value was 70.42%, and the negative predictive value was 67.47%. LOS led to a dramatic rise followed by a decrease after the initiation of the antimicrobial therapy [1.8 (1.4-2.5)] vs. [1.45 (0.2-4)] p<0.001. Conclusion: COHb levels increased at the beginning of LOS, decreasing in response to antibiotics. When used in conjunction with other sepsis biomarkers, the variation of COHb can be important in evaluating late-onset sepsis episodes in preterm infants.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Life Sciences; Health Sciences; Natural Sciences; HEMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); HEMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); Bulaşıcı hastalıklar; Genel İmmünoloji ve Mikrobiyoloji; Infectious Diseases; Immunology; General Immunology and Microbiology; Late -onset sepsis; Carboxyhemoglobin; Preterm neonates; Biomarker; CARBON-MONOXIDE; DIAGNOSIS; Late-onset sepsis; Carboxyhemoglobin; Preterm neonates; Biomarker